Analisis Pengaruh Jumlah Penduduk Perempuan Terhadap Indeks Pembangunan Manusia - Risdiana, Faraniena Yunaeni (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2020)
This study aims to determine the effect of the female population on the human development index in the province of East Java in 2017. This study uses quantitative methods with data collection techniques used are secondary data from the East Java Central Statistics Agency. From the research results it can be concluded that the total female population has almost no influence on the Human Development index. The human development index can be increased by improving the health sector, the economic sector and the education sector through the role of women, because the number of women population is almost the same as the number of men.